A Technology-Based Project with a Study that Simultaneously Evaluates STEM Awareness, STEM Self-Efficacy Beliefs, and 21st Century Skills - Dönmez Usta, Necla; Ültay, Neslihan (Science Insights Education Frontiers, 2025)
This study seeks to determine the pre-service science teachers’ STEM self-efficacy beliefs, STEM awareness, and 21st century skills at the beginning and end of a technology-based project. 28 pre-service science teachers, all aged 20-24, were included in the study. They were the 3rd or 4th grade pre-service science teachers studying at 13 universities in Turkey. From a quantitative perspective, three different data collection tools were included in the study. The first of all, the “STEM Awareness Scale”, the second data collection tool was “The Self-Efficacy Scale Related to STEM Practice”, the third data collection tool was the “Multidimensional 21st Century Skills Scale” and from a qualitative perspective a survey form including 7 open-ended questions were administered. This study was found to have contributed positively to STEM self-efficacy beliefs and 21st century abilities, and it continued to contribute positively to STEM awareness, but not statistically. It can be suggested that such activities must be designed and organized not only for pre-service teachers but also for 21st century learners such as teachers, all faculty members working at the university, and all students, etc.